PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN KEMAMPUAN KREATIVITAS SISWA DALAM PEMBELAJARAN SENI BUDAYA DAN PRAKARYA DI KELAS 3 SDN 1 SANGIANG - Ikatulislammadinah; Nur istiqomah; Ayub Qadhafi saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of the Project-Based Learning (PjBL) model on improving students’ creativity in the subject of Arts, Culture, and Crafts (SBdP) in Grade III at SDN 1 Sangiang. The research employed a quantitative approach with a quasi-experimental design, involving two classes: an experimental class using the PjBL model and a control class applying conventional learning. The instruments used included pretest and posttest creativity tests, observation sheets, and teacher interviews. The results showed a significant increase in students' creativity in the experimental class, with the average score rising from 51.58 (pretest) to 82.72 (posttest) and an N-Gain of 0.64. Meanwhile, the control class only increased from 52.15 to 67.89 with an N-Gain of 0.33. The independent t-test yielded a significance value of 0.000 (<0.05), indicating a significant difference between the two groups. Qualitative data from observations and interviews also revealed increased motivation, confidence in expressing ideas, and collaboration among students. These findings confirm that the PjBL model is effective in enhancing students' creativity and is highly recommended for application in SBdP learning at the elementary school level.